The Hyper-Wiener Index of One-pentagonal Carbon Nanocone - R. Darafsheh, M.; H. Khalifeh, M.; Jolany, H. (Current Nanoscience, 2013)
One-pentagonal carbon nanocone consists of one pentagon as its core surrounded by layers of hexagons. If there are n layers, then the graph of the molecules is denoted by Gn. In this paper our aim is to explicitly calculate the hyper-Wiener index of Gn.
Keywords: nanocone